Testing of human reactions during braking manoeuvres combining a physical test bed with virtual reality - Rajinovic, Stefan; Safikhani, Saeed; Schachner, Martin; Gstrein, Gregor; Kofler, Desiree; Schneider, Bernd; Erlinger, Nico; Pirker, Johanna; Klug, Corina (Frontiers in Future Transportation, 2022)
or the development of restraint systems, the initial posture and kinematics of the occupants immediately before the crash are essential. To predict the behaviour of vehicle occupants in pre-crash manoeuvres, volunteer tests under controlled boundary conditions to calibrate and validate active human body models are needed. The challenge in such experiments is to evoke a natural behaviour of the volunteers. The aim of this study was to investigate the potential of distractions via virtual reality (VR) in volunteer tests to study pre-crash kinematics. For this purpose, it was investigated if the volunteers are able to get immersed into the virtual reality using head-mounted displays to an extent in which they forget the laboratory environment and feel as if they are really sitting in an autonomous vehicle. A total of 27 volunteers took part in the study, and 10 different trials were carried out with each of them. In the baseline trial, no VR was displayed and the volunteers were made aware that the sled is going to start moving by a countdown. In trials 3-10, the volunteers were instructed to perform various tasks in virtual reality, which we have developed for this specific purpose. The physical platform on which they were sitting on began to move mimicking a braking maneuver as they performed a task. The peak forward head excursions resulting from the different trials were compared and showed significant differences between the baseline trial and the trials where they were distracted with VR. In contrast to our expectations, peak forward head excursions were overall significantly lower for the volunteers distracted by VR compared to the baseline trial. However, volunteers, who had significantly lower peak forward head excursions in the baseline trials showed higher peak forward head excursions in the VR trials comparable in magnitude to the other volunteers. All the volunteers answered in the questionnaire that their experience had been good and they were willing to participate in the study again. Further research is needed to understand the effect of the performed activities on the volunteer muscle activation and head excursions.